2008
DOI: 10.1002/esp.1671
|View full text |Cite
|
Sign up to set email alerts
|

Superimposition of ribbed moraines on a palaeo‐ice‐stream bed: implications for ice stream dynamics and shutdown

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 60 publications
3
48
0
3
Order By: Relevance
“…15.2A), and of one till bed at the base of the ribbed moraine. This structure most likely originated through successive subglacial thrusting under a compressional ice flow regime, as also reported by Stokes et al (2008).…”
supporting
confidence: 78%
“…15.2A), and of one till bed at the base of the ribbed moraine. This structure most likely originated through successive subglacial thrusting under a compressional ice flow regime, as also reported by Stokes et al (2008).…”
supporting
confidence: 78%
“…Consequently, a change in the basal thermal regime from warm-to cold-based conditions must have occurred after the formation of the MSGLs to enable subglacial thrusting by ice that was frozen to its bed forming the hill-hole pairs (cf., Hogan et al, 2010). Stokes et al (2008) described a similar succession of bedforms from the NW Canadian Shield, where ribbed moraines overprint MSGLs. This study concluded a significant change in ice flow velocities and in rheology of the subglacial material from water-saturated soft tills, in which the MSGLs had formed, to stiffer more dewatered tills that enabled a Fig.…”
Section: Evidence For Past Changes In Basal Conditionsmentioning
confidence: 95%
“…These regularly spaced ridges, aligned transverse to ice flow, are widely accepted to have formed subglacially and are located across considerable areas of the former Laurentide, Fennoscandian, British-Irish and Newfoundland ice sheets (NISs) (Aylsworth & Shilts, 1989;Bouchard, 1989;Clark, 1999;Clark & Meehan, 2001;Dunlop & Clark, 2006;Knight & McCabe, 1997;Lundqvist, 1969Lundqvist, , 1989Marich et al, 2005;Prest et al, 1968;Stokes, Lian, Tulaczyk, & Clark, 2008). Ridge lengths range from 100 m to 3873 m, with 63% of landforms having a typical length range of 300-1200 m (mean 447 m), which is consistent with typical lengths reported in a large representative database by Dunlop and Clark (2006).…”
Section: Ribbed Morainesmentioning
confidence: 99%
“…For example, superimposition and crosscutting landforms record significant shifts in ice flow dynamics during different bedforming events. These can be accounted for by either ice divide migrations which causes deflection of primary ice flow (Clark and Meehan, 2001), ice stream activation which can result in a new suite of landform development overprinting older ice flow patterns (Stokes et al, 2008) or may occur during deglaciation where increased topographic control causes shifts in ice flow orientation which can cut across older flow patterns (Greenwood & Clark, 2009a). Because the map records the spatial position of individual landforms, it can be used to investigate these relationships more thoroughly which will greatly improve our understanding of the dynamic behaviour of the NIS throughout the last glacial cycle.…”
Section: Landform Relationshipsmentioning
confidence: 99%